Donor Site Morbidity in Unilateral and Bilateral Transverse Musculocutaneous Gracilis (TMG) Flap Breast Reconstruction: Sensation, Function, Aesthesis and Patient-Reported Outcomes - Laura Cosima Siegwart (MDPI AG, 2021)
The transverse musculocutaneous gracilis (TMG) flap has become a popular choice for breast reconstruction. This study aimed to compare the donor site morbidity in unilateral and bilateral procedures. Patients receiving a TMG flap (January 2008–October 2019) were invited to a follow-up and grouped according to unilateral (UL group) or bilateral (BL group) breast reconstruction. Outcome criteria included sensation, function and aesthesis of the thighs. Patient-reported outcomes were surveyed using validated questionnaires. The number and kind of refinement procedures for aesthetic purposes on the donor thighs were evaluated. Thirty-eight patients with 59 TMG flaps were included in the study (UL group: n = 17, BL group: n = 21). Normal to slightly diminished superficial skin sensation was maintained in most of the thigh skin (98.4%). Strength and mobility were without impairment in >80% of the thighs in both groups. Thigh symmetry was achieved in both groups. Symmetrisation procedures were significantly more often performed in the UL group (p = 0.005). The total number of refinement procedures was similar in both groups. Patient-reported outcomes were similar with good appearance of the thighs and scars, excellent function and low pain levels. The TMG flap offers excellent function and sensation on the donor thigh. Thigh symmetry and good patient satisfaction may be achieved in both unilateral and bilateral breast reconstructions.